A new species of adesmia (Leguminosae, papilionoideae, dalbergieae) from Southern Brazil, with notes on leaf anatomy - Monteiro, Thiago Cobra E. [UNESP]; Vieira Iganci, João Ricardo; Seixas, Diana Pacheco [UNESP]; Rodrigues, Tatiane Maria [UNESP]; Fortuna-Perez, Ana Paula [UNESP] (Magnolia Press, 2021)
A revisional taxonomic study of Adesmia subg. Adesmia ser. Bicolores has unveiled a new species from southern Brazil. Adesmia miottoae is described and illustrated here. Its geographic distribution, phenology, conservation status and morphological similarities with its closest relatives, Adesmia punctata and A. incana, are presented. The species is distinguished by glandular trichomes covering all the aerial parts of the plant, except the corolla. These trichomes are shorter than those of Adesmia punctata. Additionally, a detailed anatomical description of the leaflet blade is provided.
Keywords: Adesmia clade; Anatomy; Fabaceae; Rio Grande do Sul; Taxonomy